State crises, globalisation, and national movements in north-east Africa - Jalata, Asafa, 1954- (Routledge, 2004)
This book demonstrates that the crises of the Horn states stem from their political behaviour and structural forces.
Title from PDF title page (viewed 23 Nov., 2009).
Keywords: State, The.; Nationalism -- Africa, Northeast.; Globalization -- Political aspects -- Africa, Northeast.; Africa, Northeast -- Politics and government -- 1974-; Africa, Northeast -- Ethnic relations.; État.; Nationalisme -- Afrique du Nord-Est.; Mondialisation -- Aspect politique -- Afrique du Nord-Est.; Afrique du Nord-Est -- Politique et gouvernement -- 1974-; Afrique du Nord-Est -- Relations interethniques.; POLITICAL SCIENCE -- Political Process -- General.; Ethnic relations; Globalization -- Political aspects; Nationalism; Politics and government; State, The; Northeast Africa; Since 1974